Empréstimo consignado: práticas abusivas diante do Código de Defesa do Consumidor e sua interpretação pelo poder judiciário - Paula Junior, Joel Gomes de (2024)
This dissertation examines the importance of consumer law in Brazil, highlighting the historical and legislative evolution that led to the creation of payroll loans and the Consumer Protection Code. It also analyzes the implementation of the National Consumer Relations Policy and the principles established by the Consumer Protection Code to regulate relations between consumers and suppliers. The study explores the complexity of abusive commercial practices, focusing on the phenomenon of unsolicited payday loans and consumer vulnerability. Essential concepts of consumer vulnerability, including aggravated (hypervulnerability) and ultravulnerability, are discussed. Payroll loan contracts are analyzed, with emphasis on the utilization of dark patterns in design and manipulative strategies. Furthermore, the predictability of free samples as a civil sanction within the scope of the Consumer Protection Code is examined, analyzing its role and application in this specific context. Additionally, two main issues are addressed: illicit enrichment as a factor that impedes the application of forfeiture sanctions and the absence of requirements enabling consumers to demand the retention of amounts voluntarily deposited by banks. This dissertation offers a critical analysis of these issues.